PENGARUH DEBT TO EQUITY RATIO (DER) DAN NET PROFIT MARGIN (NPM) TERHADAP RETURN SAHAM PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2018 - Rindani, Ana (Growth, 2024)
This study aims to (1) to determine the influence of Debt to Equity Ratio (DER) and Net Profit Margin (NPM) influence partially on stock return (2) to know the influence of Debt to Equity Ratio (DER) and Net Profit Margin (NPM) influence simultaneously on stock return (3) to know among Debt to Equity Ratio (DER) and Net Profit Margin (NPM) most Dominant effect on stock return. The method used in this research is qualitative method. The result of research is multiple linear regression equation Y = 0,777 – 1,166 X1 – 0,007 X2 + e. partially Debt to Equity Ratio (DER) have negative significant effect with value equal to -2,194, equal to -2,026, Net Profit Margin (NPM) have significant negative effect with value equal to -2,701, equal to -2,026. Simultaneously Debt to Equity Ratio (DER) and Net Profit Margin (NPM) influence to stock return with value equal to 3,25, equal to 3,25. The most dominant variable in this research is Net Profit Margin (NPM) with value -2,701.